Corruption Control in the Developed World - Fabrizio Di Mascio; Simona Piattoni (Politics and Governance, 2020)
Conventionally considered a developmental trait that would tend to disappear with the increase of wealth and the stabilization of democracy, corruption is rampant not just among developing countries and recent democracies, but also in mature democracies and developed countries. This editorial introduces the thematic issue and considers what the contributions tell us about new approaches to corruption control in the developed world. It also outlines avenues for future research in the field of corruption control.